Yeast diversity and native vigor for flavor phenotypes. Issue 3 (March 2015) - Carrau, Francisco; Gaggero, Carina; Aguilar, Pablo S.
Highlights Flavor traits matter most for yeast in food biotechnology and winemaking. Increasing strain diversity will increase flavor complexity of wine. Manipulating primary metabolic pathways has a negative impact on flavor compounds. The Yeast Flavor Diversity Screening method will impact upon food biotechnology.